The Contributions to Virulence of the Effectors Eop1 and DspE Differ Between Two Clades of Erwinia tracheiphila Strains - Olakunle I. Olawole; Qian Liu; Chiliang Chen; Mark L. Gleason; Gwyn A. Beattie (Molecular Plant-Microbe Interactions, 2021)
Strains of Erwinia tracheiphila, causal agent of bacterial wilt of cucurbits, are divided into distinct clades. Et-melo clade strains wilt Cucumis spp. but not Cucurbita spp., thus exhibiting host specificity, whereas Et-C1 clade strains wilt Cucurbita spp. more rapidly than Cucumis melo, thus exhibiting a host preference. This study investigated the contribution of the effector proteins Eop1 and DspE to E. tracheiphila pathogenicity and host adaptation. Loss of eop1 did not enable Et-melo strains to infect squash (Cucurbita pepo) or an Et-C1 strain to induce a more rapid wilt of muskmelon (Cucumis melo), indicating that Eop1 did not function in host specificity or preference as in the related pathogen E. amylovora. However, overexpression of eop1 from Et-melo strain MDCuke but not from Et-C1 strain BHKY increased the virulence of a BHKY eop1 deletion mutant on muskmelon, demonstrating that the Eop1 variants in the two clades are distinct in their virulence functions. Loss of dspE from Et-melo strains reduced but did not eliminate virulence on hosts muskmelon and cucumber, whereas loss of dspE from an Et-C1 strain eliminated pathogenicity on hosts squash, muskmelon, and cucumber. Thus, the centrality of DspE to virulence differs in the two clades. Et-melo mutants lacking the chaperone DspF exhibited similar virulence to mutants lacking DspE, indicating that DspF is the sole chaperone for DspE in E. tracheiphila, unlike in E. amylovora. Collectively, these results provide the first functional evaluation of effectors in E. tracheiphila and demonstrate clade-specific differences in the roles of Eop1 and DspE.[Graphic: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.